Improved cycling stability of V2O5 modified spinel LiMn2O4 cathode at high cut-off voltage for lithium-ion batteries - Radzi, Zulhadi Iskandar (Wiley, 2022)
Spinel lithium manganese oxide, LiMn2O4 coated with V2O5 layer (labeled as LMO-VO) has been developed and its electrochemical performances as cathode material for lithium-ion batteries has been evaluated at high cut-off voltage (>4.5 V vs. Li/Li+) and compared with pristine LiMn2O4 (labeled as LMO). The crystal structure investigations show that LMO-VO has longer Li-O bond length for fast Li-ion diffusion kinetic process. The scanning electron microscopy results indicate that LMO-VO has finer particles and the V2O5 layer has been successfully coated on the LMO surface uniformly. The highly conductive V2O5 coating layer enhances the ionic conductivity of the LMO cathode, as evidenced by the significant drop of R-ct value from the Nyquist plot. Under high operating voltage, the cell employed with coated LMO shows exceptional cycling performance in capacity retention and potential difference. After 300 cycles, the capacity retention per cycle has been boosted from 99.90% to 99.94% by adopting the V2O5 coating layer. In addition, surface coating with V2O5 stabilizes the potential difference at very minimal change for a longer period. This convincingly proves that the V2O5 coating layer not only protects against hydrofluoric acid (HF) attack and greatly restrains the increase of cell polarization at high voltage.